Risk factors of neonatal mortality of referred babies with birthweight of 1000- < 2500 grams - Ekawaty Lutfia Haksari, Dian Murni Wardhani, Setya Wandita (Universitas Gadjah Mada, 2009)
Background: Almost 16% from all of the total births in the developing countries are low birthweight babies. Low birthweight babies are an important contribution in neonatal mortality and morbidity worldwide, and contribute to almost 70% of the total neonatal deaths. Proportion of the low birthweight babies in the developing countries is 90% of the total low birthweight babies around the world, which is 20 million annually. Mortality of babies weighing 1000-< 2500 grams in Dr. Sardjito Hospital reached 51.4%, and that of referred babies was 74.6%. Objectives: This research was aimed to find out and measure the risk factors that contribute to the mortality of referred low birthweight babies in the neonatal period. Methods: A hospital-based research with case-control study design was done to discover the risk factors that related to the neonatal mortality of the referred babies with birthweight of 1000- < 2500 grams. Data were collected from babies medical records treated in the Maternal-Perinatal Installation of Dr. Sardjito Hospital in 2005 to 2007. Target population of this research was the mentioned above who died at the age of 0-28 days. Variable analysis to find out the correlation between the risk factors and the mortality used odds.ratio (OR), 95% confidence interval (95% CI), and the significance level with Chi-square test. To measure the risk factors that contributed on the mortality multivariate logistic regression analysis was used. Result: This study involved 190 babies (95 cases and 95 control) weighing between 1000 and < 2500 grams, who were referred to Dr. Sardjito Hospital. Several subjects were excluded, 23 babies because of going home on selfrequest, 24 because of incomplete status, 76 because of severe congenital anomaly, and 34 were extremely low birthweight babies. Sepsis (OR: 5.054, 95%CI2.433-11.198), HMO(OR:4.461, 95%CI1.595-10.497), hypoglycemia (OR: 3.358, 95%CI1.679-6.715), and hypothermia (OR: 2.221, 95%CI1.082-4.560) were the risk factors of mortality. Conclusion: Sepsis, HMO, hypoglycemia, and hypothermia increased the mortality risk of babies weighing 1000-< 2500 grams referred to Dr. Sardjito Hospital, Yogyakarta. Key words: low birthweight baby -risk factor -referral -neonatal death